A review of the configuration of bordered pits to stimulate the fluid flow - Usta, Ilker (Maderas. Ciencia y Tecnología, 2014)
As the bordered pits have generally been thought to have an influence on the refractory nature of softwoods, structural behaviour of this conducting pathways is discussed according to the published literature. Various theories on the role of bordered pits to axial flow are expounded in respect to preservative treatment. Pit aspiration is also reviewed.